No man is an island a portrait of Singapore's Lee Kuan Yew - Minchin, James (Allen & Unwin Australia Pty Ltd, 1990)
This biography of Lee Kuan Yew, former Premier of Singapore, provides a profile for all who would seek to understand the "economic miracle" of Singapore and the man who led the island state for so long.